Fast room temperature lability of aluminosilicate zeolites - Christopher J. Heard (Nature Portfolio, 2019)
While aluminosilicate zeolites are of interest for many applications, the affect of water on zeolite stability in mild aqueous conditions has yet to be established. Here, using ab initio calculations and NMR spectroscopy, the authors show that covalent bonds in the zeolite chabazite are labile when in contact with neutral liquid water.